Research Project-based on Level of Inquiry Terhadap Keterampilan Pemecahan Masalah Sains Pada Mahasiswa - Fuadi, Muhammad; Asriyadin, Asriyadin (STKIP Taman Siswa Bima, 2025)
This study aims to determine: 1) Differences in Science Problem-Solving Skills Among Students who were given the Research Project Model treatment in terms of intrapersonal and interpersonal aspects; 2) The interaction between the Research Project Model and Inquiry Level on Science Problem-Solving Skills Among Students; 3) Differences in Science Problem-Solving Skills among Students who were given the Research Project Model treatment in terms of Intrapersonal and Interpersonal aspects who had High Inquiry; and 4) Differences in Science Problem-Solving Skills among Students who were given the Research Project Model treatment in terms of Intrapersonal and Interpersonal aspects who had Low Inquiry. The type of research used was experimental research with a 2 x 2 level research design. The research was conducted at STKIP Taman Siswa Bima in the PGSD Study Program in Semester V with a population of 540 students, so that the sample taken at a confidence level of 90% and a margin of error of 15% was 60 students. The results showed that 1) there was a significant difference in science problem-solving skills between students who used the intrapersonal model (M1) and the interpersonal model (M2), with M1 showing higher results; 2) there was a significant interaction between the Research Project model and the inquiry level, with students with high inquiry showing better results than those with low inquiry; 3) students who used the intrapersonal model with high inquiry (M1C1) had better problem-solving skills than those who used the interpersonal model with high inquiry (M2C1); and 4) there was no significant difference between the intrapersonal and interpersonal models at low inquiry levels (M1C2 and M2C2). These findings emphasize the importance of an intrapersonal approach in project-based learning and the need to apply challenging inquiry levels to improve students' science problem-solving skills.